Is it Really Nature That Restores People? A Comparison With Historical Sites With High Restorative Potential - Scopelliti, Massimiliano; Carrus, Giuseppe; Bonaiuto, Marino (Frontiers in Psychology, 2019)
Research on restorative environments has showed the healthy outcomes of nature experience, though often by comparing attractive natural to unattractive built environments. Some studies indeed showed the restorative value of artistic/historical settings. In a quasi-experimental study involving 125 participants in Rome, Italy, a natural and a built/historical environment, both scoring high in restorative properties, were evaluated in a natural, built/historical, or neutral setting. Accordingly toIn accordance with the Biophilia hypothesis and the Attention Restoration Theory (ART), we expected hypothesised: a higher restorative potential of nature also when compared to built/historical environments; a moderation effect of on-site experience on perceived restorative potential (PRP) of both environmental typologies; higher levels of restorative properties of the environment for on-site vs. not on-site respondents; and a mediation effect the restorative properties of the environment in the relationship between time spent on-site and PRP. In a quasi-experimental study, a natural and a built/historical environment, both scoring high in restorative properties, were evaluated in a natural, built/historical, or neutral setting. However, a moderation effect of on-site experience on perceived restoration of different environmental typologies was also hypothesized, through the increase in the perception of the restorative properties of the environment. Finally, the role of time spent in restorative environments in the restoration process was analysed. In a quasi-experimental study, a natural and a built/historical environment, both scoring high in restorative properties, were evaluated in a natural, built/historical, or neutral setting. Results supported the Biophilia hypotheseis. In addition, different psychological processes leading to restoration emerged for the natural and the built/historical environment. Theoretical implications for ART and practical applications for an integrative urban design with natural and historical elements implications are discussed.